PENERAPAN STRATEGI ACTIVE LEARNING TIPE QUIZ TEAM DALAM MENINGKATKAN AKTIVITAS BELAJAR MATA PELAJARAN EKONOMI - Susi Hardillah; Junaidi H. Matsum; Maria Ulfah (Universitas Tanjungpura, 2021)
AbstractThis study aims to improve student learning activities by applying the Quiz TeamType Active Learning method and the lecture method. This type of research is anexperimental research method. This study uses three stages carried out. Collectdata, analyze and calculate percentages. The result of the percentage of the lecturemethod in the first meeting was 30.55% and the second meeting was 38.325. Whilethe Active Learning method for the Quiz Team type, the percentage of meeting 1 is58.88% and meeting 2 is 68.88%. Thus there are differences in student learningactivities. Based on the results of the study, it can be concluded that research usingActive Learning learning type Quiz Team further enhances student learningactivities in class X Accounting at SMAN 3 Pontianak.Keyword: Active Learning tipe Quiz Team, Student Learning Activities